PSYCHOSOCIAL ASSISTANCE AND STRENGTHENING THE IMPLEMENTATION OF LEARNING MODULES FOR ELEMENTARY SCHOOL DURING THE COVID-19 PANDEMIC AT SD INPRES 1 SORONG - Irham Miftakhul Jannah; Yeni Withdianti (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2021)
This community service is aimed to assist elementary school quality programs to assist students in learning activities in the pandemic era by using prepared learning modules. Guidelines for the pursuit of elementary school quality programs through psychosocial assistance programs and strengthening the implementation of elementary school learning modules in 3t and non-3t areas during the covid-19 pandemic period. The activity was carried out at SD Inpres 1, Sorong Regency and PP IPPNU partners in providing assistance. The problems that arise in the implementation of Online Learning (PJJ) are the difficulty of teachers in managing PJJ and being focused on completing the curriculum. As a result of curriculum changes and the compression of learning materials lead the potential of children, especially those in 3T areas of Indonesia lose the chance to learn. The lack of facilities creates obstacles in the learning process, such as not all students have smart phones, and the limited capacity of parents to assist children in learning so that children can not study optimally.